The suite of lumped GR hydrological models in an R package. (August 2017) - Coron, L.; Thirel, G.; Delaigue, O.; Perrin, C.; Andréassian, V.
Abstract: Lumped hydrological models are catchment-scale representations of the transformation of precipitation into discharge. They are widely-used tools for real-time flow forecasting, flood design and climate change impact assessment, and they are often used for training and educational purposes. This article presents an R-package, airGR, to facilitate the implementation of the GR lumped hydrological models (including GR4J) and a snow-accumulation and melt model. The package allows users to calibrate and run hourly to annual models on catchment sets and to analyse their outputs. While the core of the models is implemented in Fortran, the user can manage the input/output data within R. A number of options and plotting functions are proposed to ease automate tests and analyses of the results. The codes are flexible enough to include external models, other calibration routines or efficiency criteria. To illustrate the features of airGR, we present one application example for a French mountainous catchment.